Analysis of The Dose-Response Relationship Between Duration and Posture of Sitting on The Intensity of Lower Back Pain in Medical Students: A Longitudinal Study With A Repeated Measures Approach - Muh. Rezky Ananda Larekeng; Delvira Florencya Rahmat; Dyajeng Ciptaningrum Putri Widada; Delviansyah Lamusu; Fitrianti Syamsuddin; Jufri Febriyanto Poetra (Universitas Pahlawan Tuanku Tambusai, 2026)
Low back pain (LBP) is common among medical students due to prolonged sitting and non-ergonomic posture, which increase intradiscal pressure and paraspinal muscle tension. To assess the dose–response relationship between sitting duration, sitting posture, and LBP intensity in preclinical students longitudinally. A 14-day study involving 201 students with three measurements (Pre, Mid, Post). Sitting duration was assessed using DDA, posture using ASPQ, and LBP using BPBM–VAS. Analysis used GEE AR(1) to assess main effects and interactions. Sitting duration (p = 0.018), posture (p < 0.001), DDA-ASPQ interaction (p = 0.048), and TIMEDDA, ASPQ interaction (p = 0.023) significantly affected LBP. Good posture reduced pain, while high sitting duration with poor posture increased progressive pain. Results were consistent in the Gamma–Log and Tweedie–Log models. This study shows that lower back pain is influenced by the interaction between sitting duration and posture. Prolonged sitting with poor posture increases pain, while ergonomic posture reduces its impact. These findings emphasise the importance of ergonomic education, movement breaks, and learning facilities that support pain prevention.